ANALYSIS OF THE EFFECT OF ROTATTION AND RATE OF MASS LOSS ON THE EVOLUTION OF MASSIVE STARS - Tri Eka Putra, Dio
The evolution of stars takes a long time compared to the age of humans, with a range of millions to billions of years. Nobody can see and observe the evolution of stars from the beginning of formation to the end of a star. For that, a theory and model can explain the evolutionary process of a star by observing the condition of each star at this time. Star evolution theory is built on star observations with relatively similar masses than their respective conditions. Differences and equations based on observations made will be fundamental to building theories and models of stellar evolution. Therefore, people do not have to wait for an evolutionary star to build a stellar theory of evolution. Star Mass is the biggest and dominant factor for the evolutionary stages that a star will pass through, so there are several categories in the grouping of stellar evolution based on stellar mass. The massif star has a mass of M stars ? 8M ?, this star will pass through the phase of the main sequence, subgiant, supergiant, Wolf-Rayet star, Supernova, and neutron star or black hole. In this final assignment, the evolution of the Massif stars will be discussed with a certain mass. Stellar evolution tracks are modelled in HR diagram, by inserting the physical parameters in the form of initial masses of 8 M?, 10 M?, 12 M?, 15 M?, 20 M?, 30 M?, 35 M?, 40 M?, 60 M?, 80 M?, and 100 M?, star rotation speed (v = 300 km/s), metallicity (Z = 0.02). It is then reviewed the rotation effect of evolutionary traces on each star. Stellar Evolutionary Trail modeling was created using the Linux-based evolution numeric Code of MESA (Modules for Experiment in Stellar Astrophysics).